2004
DOI: 10.1007/s00210-004-0866-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of a novel selective 5-hydroxytryptamine 1B receptor antagonist, AR-A000002

Abstract: The terminal 5-HT(1B) autoreceptors have attracted great pharmacological interest since they are potential targets for compounds modifying serotonergic neurotransmission. In the present work the in vivo biochemical properties of AR-A000002 ((R)-N-[5-methyl-8-(4-methylpiperazin-1-yl)-1,2,3,4-tetrahydro-2-naphthyl]-4-morpholinobenzamide), a novel selective 5-HT(1B) receptor antagonist, are reported. The effects of AR-A000002 on: 5-HT metabolism was measured as the ratio between 5-HIAA and 5-HT concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…K i,plasma AZD3783 plasma concentration required for half-maximum receptor occupancy binding to the receptor and residual binding of endogenous 5-HT released after AZD3783 administration. However, increases in endogenous 5-HT observed with 5-HT 1B antagonists in microdialysis studies are moderate (0.2-to 2-fold; Stenfors et al 2004;Dawson et al 2006) when compared to the marked elevation in 5-HT release induced by fenfluramine (20-to 35-fold; Udo de Haes et al 2006). Future studies with [ 11 C]AZ10419369 and a pharmacological manipulation that induce more moderate elevations in endogenous 5-HT levels are required to clarify the contribution of residual binding of endogenous 5-HT to the occupancy measured with AZD3783.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…K i,plasma AZD3783 plasma concentration required for half-maximum receptor occupancy binding to the receptor and residual binding of endogenous 5-HT released after AZD3783 administration. However, increases in endogenous 5-HT observed with 5-HT 1B antagonists in microdialysis studies are moderate (0.2-to 2-fold; Stenfors et al 2004;Dawson et al 2006) when compared to the marked elevation in 5-HT release induced by fenfluramine (20-to 35-fold; Udo de Haes et al 2006). Future studies with [ 11 C]AZ10419369 and a pharmacological manipulation that induce more moderate elevations in endogenous 5-HT levels are required to clarify the contribution of residual binding of endogenous 5-HT to the occupancy measured with AZD3783.…”
Section: Discussionmentioning
confidence: 96%
“…As shown with the microdialysis technique, centrally active 5-HT 1B receptor antagonists increase extracellular levels of 5-HT (Stenfors et al 2004;Dawson et al 2006). It may therefore be assumed that elevation in 5-HT levels in response to AZD3783 administration may reduce radioligand binding to brain 5-HT 1B receptors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This mechanism also has the potential to provide a rapid onset of clinical efficacy without the liabilities associated with SSRIs (Moret and Briley, 2000;Slassi, 2002). Animal models such as serotonin agonist-induced guinea pig hypothermia (Maj et al, 1988) and guinea pig pup separation-induced vocalization (Hagan et al, 1997;Hudzik et al, 2003;Stenfors et al, 2004;Dawson et al, 2006) were developed to screen and evaluate the pharmacology of serotonergic agents such as 5-HT 1B receptor antagonists. Selective 5-HT 1B antagonists such as (R)-N- [5-methyl-8-(4-methylpiperazin-1-yl)-1,2,3,4-tetrahydro-2-naphthyl]-4-morpholinobenzamide (AR-A000002) (Hudzik et al, 2003) and 1-[6-(cis-3,5-dimethylpiperazin-1-yl)-2,3-dihydro-5-methoxyindol-1-yl]-1-[2Ј-methyl-4Ј-(5-methyl-1,2,4-oxadiazol-3-yl)biphenyl-4-yl]methanone hydrochloride (SB-616234-A) (Dawson et al, 2006) have been shown to elevate serotonergic neurotransmission in vivo and exhibit effects indicative of antidepressant and anxiolytic properties in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Rats and mice are being used for almost all models. However, potential new drug targets often show species differences (Oksenberg et al 1992;Pradier et al 1995) and pharmacology, which differs between murids and humans (Beresford et al 1991;Stenfors et al 2004). In many cases, guinea pig receptors display higher homology and pharmacology more similar to their human counterparts as compared to murid receptors.…”
Section: Introductionmentioning
confidence: 95%